Desert ecology - Cleminson, Neil ([S.l.] : The Open University, 1974)
Defines the plants' and animals' life in the desert
Specimens of photographs provided by The Royal Botanical Garden, Kew
Presenter: Irene Ridge, Wilma George
Keywords: Desert ecology; Ecology -- Study and teaching